Efektivitas Arang Aktif Sekam Padi dan Kulit Pisang Kepok sebagai Adsorben pada Pengolahan Air Sungai Sekanak 26 Ilir Palembang - Satya, Iqram Pra; Legiso, Legiso; Juniar, Heni (Jurnal Teknologi Riset Terapan, 2024)
Purpose: This study aimed to evaluate the effectiveness of activated charcoal from rice husks and Kepok banana peels in improving Sekanak River water quality, focusing on pH stabilization and iron (Fe) removal. Methodology: Activated charcoal was produced via carbonization, followed by sieving and characterization based on the moisture content, ash content, and volatile matter. Adsorption tests were conducted using varying adsorbent masses (35–55 g), and the water quality parameters (pH and Fe) were measured before and after treatment. Results: Both adsorbents met the SNI 06–3730–1995 standards: moisture content <15%, ash <10%, and volatile matter <25%. Using 55 g of banana peel charcoal reduced the Fe content from 0.40 mg/L to 0.049 mg/L and increased the pH from 6.59 to 7.27. Rice husk charcoal increased the pH to 7.16. Banana peel charcoal exhibited slightly better performance in both iron removal and pH improvement. Conclusion: Activated charcoal from banana peels and rice husks effectively improved water quality. Both met national standards, with banana peel charcoal offering slightly superior performance in reducing Fe and stabilizing pH. Limitation: This study was limited to laboratory-scale experiments on a single water source, without long-term or real-field testing. Only one activation method was used. Contribution: This study supports the use of low-cost, eco-friendly materials such as rice husks and banana peels as effective adsorbents for water treatment, offering sustainable solutions particularly suited for rural or resource-limited areas.